Land Policy for Flood Risk Management—Toward a New Working Paradigm. Issue 4 (5th April 2022) - Potočki, K.; Hartmann, T.; Slavíková, L.; Collentine, D.; Veidemane, K.; Raška, P.; Barstad, J.; Evans, R.
Abstract: Flood risk management (FRM) aims to integrate necessary technical measures with environmental and societal approaches. Focusing on the process and governance of how to plan, implement, and maintain solutions therefore becomes essential. Among the different stakeholders, landowners are a key group to be considered. This contribution elaborates on the interconnections between land policy, FRM and private land ownership. It is based on the European COST Action network LAND4FLOOD, which brings together academics and stakeholders from various disciplines and more than 35 countries. We argue for a less project oriented and more process oriented approach, a focus on land management and more emphasis on small‐scale measures. This represents a break with some of the recent working paradigms of FRM. Plain Language Summary: Flood risks are expected to increase in the future due to the combined effects of climate change, land use change and population growth. New approaches are needed to complement conventional flood risk management (FRM) based on engineering solutions and project‐based approaches. In this Commentary we present the findings of the LAND4FLOOD project, which is based on 4 years of research by academics and stakeholders from diverse backgrounds and disciplines: engineering, societal and environmental. We identify three main issues that should be considered to gain support from different stakeholders for the successful implementation of flood risk measures. First, more process orientation in planning and preparing measures is needed. Second, a comprehensive and inclusive land policy is crucial for flood retention. Third, it is important to start at the local scale. Key Points: Flood risk management needs more focus on processes to plan and implement measures Comprehensive and inclusive land policy is crucial for flood retention Starting with the local scale is essential throughout the whole process of planning and implementation of flood management measures